Higher education in Japan : can the system change? : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Japanese Sociology at Massey University, Palmerston North, New Zealand - Burgiss, Angela (Massey University, 1999)
The topic for this thesis is: The Reform of Higher Education in Japan- Can the System Change? Since the establishment of the university system in the Meiji Restoration. Japan's higher education system has been undergoing a series of changes and reforms that continue to the present day. Rapid social and economic changes and the quantitative expansion of higher education in the post-war period have greatly effected the affaire in education. There has not, however, been the same improvements in the quality of education received at the higher levels. The effects of the problems are widely reflected in the lower levels of education and society as a whole, through the increase in juvenile delinquency, violence in schools, and examination hell. There are so many issues discussed within the reform debates that, for the purpose of this thesis, I have chosen to focus five problems that have continued to plague the Japanese Higher Education system. They are:- • Academic credentialism- The social climate in which too much value is placed on the educational background of the individuals: • The hierarchy of and within the institutions of higher education; • The quality in undergraduate education and the lack of graduate education • Selection methods: the excessive competition for university entrance examinations; • The Control of Education by the Government. These problem areas are interwoven with each other, each having a strong effect on the other. The complexity and interrelationship of these issues are the starting point in the attempt to understand why there has not been any solution throughout the reform efforts of the past three decades. Various education missions and councils have all pointed out these problems and made recommendations as to how their effects could be alleviated, but still there is no change. Between the time the recommendations are made to the time when reform measures can be implemented, something is going wrong, blocking the chance to make the substantial changes necessary to bring about higher education reform in Japan. Although the need for reform widely recognised both inside and outside Japn, the three major reform attempts in the past (Meiji, Occupation, and 1980s Nakasone Campaign), have not been successful in eliminating the problems that remain visible into the 1990s. Although some significant changes have been made, these reform attempts have failed to solve the major problems in higher education, and in some cases they have made them more visible. In other cases they have only made conceptual changes without dealing with the fundamental issues Education reform, is now (late 1990s) a major national issue. The current reform stems from a growing sense in Japan that higher education is neither responding to new national needs in a changing world nor to the changing concerns of Japanese youth. However, the Japanese must not only deal with the problems evident in society at present, but they must also face a future with fewer students of university age due to the low birth rate and ageing population. As a result of this demographic trend, enrolments at the university will decline steadily after peaking in the early 1990s. From now on, universities will have to market themselves to potential students on the basis of specialisation and differentiation. The purpose of my thesis is to discuss whether or not the higher education system in Japan can reform itself into one that will meet the needs of the 21st Century. By outlining the development of the five problems I mentioned above, and looking at why have previous reform attempts to solve these problems have failed, I hope to come to a conclusion as to why the reform efforts to alleviate these problems have not been successful, and ultimately answer the question "Can the System Change?".
Some Japanese language throughout
Keywords: Japan Higher Education